2015
DOI: 10.3109/10837450.2015.1055766
|View full text |Cite
|
Sign up to set email alerts
|

Sinomenine hydrochloride-loaded dissolving microneedles enhanced its absorption in rabbits

Abstract: Sinomenine hydrochloride-loaded dissolving microneedles (SH-DM) were fabricated by maltose and poly-lactic-co-glycolic acid using a casting method. The mechanical strength of SH-DM was investigated by an insertion test. In vivo transdermal absorption experiment was performed to evaluate the percutaneous absorption of SH-DM, sinomenine hydrochloride gel (SH-G) was used as a control. The results demonstrated that prepared SH-DM was morphologically intact with sufficient mechanical strength after inserting into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…However, oral SH can cause adverse reactions such as gastrointestinal irritation and a first-pass effect. Injections are more expensive and require professional training for administration (Wu et al, 2016;Arya et al, 2017). Transdermal drug delivery is an attractive alternative to oral administration or injection, and early studies confirmed that it could overcome the above-mentioned problems (Prausnitz & Langer, 2008;Romgens et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, oral SH can cause adverse reactions such as gastrointestinal irritation and a first-pass effect. Injections are more expensive and require professional training for administration (Wu et al, 2016;Arya et al, 2017). Transdermal drug delivery is an attractive alternative to oral administration or injection, and early studies confirmed that it could overcome the above-mentioned problems (Prausnitz & Langer, 2008;Romgens et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This also eliminates any potential risk of biohazardous sharp waste. Sustained delivery from the MN baseplates is also possible for small molecules (Wu et al, ). DMN has been widely used to deliver hydrophilic drugs, as such molecules are easy to mix with water‐soluble polymers used for DMN preparation (Donnelly et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the control of morphine was very strict, accordingly, it is difficult to be obtained. It was reported by Wu et al, that the external standard method was used to determine the plasma concentration of sinomenine hydrochloride 19. The representative chromatograms of blank rabbit plasma, and blank rabbit plasma spiked with sinomenine hydrochloride were shown in Figure 2A.…”
Section: Resultsmentioning
confidence: 99%